Eg9 TB Mat Chap15
Eg9 TB Mat Chap15
Eg9 TB Mat Chap15
Equations
By studying this lesson you will be able to;
² solve linear equations containing brackets,
² solve linear equations containing fractions,
² solve simultaneous linear equations when the coefficient of one unknown is
equal in both equations.
Linear equations
Do the following exercise to recall the facts that you have learnt in previous grades
on solving linear equations.
Review Exercise
Solve the following linear equations.
a. x + 12 = 20 b. x – 7 = 2 c. 5 + m = 8
d. 2x = 16 e. – 3x = 6 f. 2p + 1 = 5
x 2p
g. 3b – 7 = 2 h. =3 i. =6
2 2
j. m – 1 = 8 k. 2 (x + 3) = 11 l. 3 (1 – x) = 9
5
You may have observed that there are some equations with brackets in the review
exercise. In this lesson we expect to learn how to solve linear equations with two
types of brackets. Let us first consider how to construct a linear equation with
several brackets and find its solution.
73
For free distribution.
“The result of adding three to a certain number and subtracting one from twice this
value, and finally multiplying the resulting value by five and adding two is equal
to 47”.
Let us consider how to construct an equation using the above information and then
solve it.
If the number is x, when 3 is added, we obtain x + 3.
Twice this expression can be written as 2(x + 3) using parentheses.
The expression that is obtained when 1 is subtracted from this is 2(x+3) −1.
Using curly brackets to write five times this expression we obtain,
5{2 (x + 3) – 1}
It is given that when 2 is added to this expression it is equal to 47. Therefore,
5{2 (x + 3) – 1} + 2 = 47
Now, by solving this equation, let us find the value of the number (x).
5{2x + 5} + 2 = 47.
Now, simplifying the expression with curly brackets we obtain
10x + 25 + 2 = 47.
10x + 27 = 47
Subtracting 27 from both sides we obtain,
10x + 27 – 27 = 47 – 27.
That is, 10x = 20 .
Dividing both sides by10 we obtain,
10x 20
10 = 10
x=2
Therefore, the number is 2.
Let us consider a few more examples of equations with brackets to improve our
skills of solving such equations.
74
For free distribution.
Example 1
Solve 2{3 (2x – 1) + 4} = 38'
2{3 (2x – 1) + 4} = 38 (dividing both sides by 2)
2 2
3(2x – 1) + 4 = 19
6x – 3 + 4 = 19 (simplifying the expression with parentheses)
6x + 1 = 19
6x + 1– 1 = 19 – 1 (subtracting 1 from both sides)
6x = 18
6x 18
6 = 6 (dividing both sides by 6)
x=3
Example 2
5{4 (x + 3) – 2 (x – 1)} = 72
5{4x + 12 – 2x + 2} = 72 (simplifying the expression with parentheses)
5{2x + 14} = 72
10x + 70 = 72 (simplifying the expression with curly brackets)
10x + 70 – 70 = 72 – 70 (subtracting 70 from both sides)
10x = 2 (dividing both sides by 10)
10 10
1
x=
5
Exercise 15.1
Solve the following equations.
Therefore, x – 10 = 12
5
Now, let us solve this equation and find x.
x – 10 = 12
5
Multiplying both sides of the equation by 5,
5 x – 10 = 12 5
5
x – 10 = 60
Adding 10 to both sides,
x – 10 +10 = 60 +10
x = 70
Therefore, the vendor bought 70 mangoes to sell.
Let us study the following examples to learn more on solving linear equations with
fractions.
Example 1
Solve x + 3 = 15'
2
x+3
2 = 15
x+3
2 2 = 15 2 (multiplying both sides by 2)
x + 3 = 30
76
For free distribution.
x + 3 – 3 = 30 – 3 (subtracting 6 from both sides)
x = 27
Example 2
y y
Solve – = 9'
2 3
y y
– =9
2 3
y y
6 –6 = 9 6 (multiplying both sides by 6, the L.C.M. of the
2 3
denominators 2 and 3 )
3y – 2y = 54
y = 54
Example 3
m
Solve 2 – 1 = 10'
3
m
2 – 1 = 10
3
2 m
= 10 (dividing both sides by 2)
2 3 –1
2
m
–1=5
3
m
– 1 + 1 = 5 + 1 (adding 1 to both sides)
3 m
=6
3
m
= 6 3 (multiplying both sides by 3)
3
3
m = 18
Note: When solving equations, it is not necessary to write the reason for each
simplification.
Exercise 15.2
Solve each of the following equations.
y+8
a. x – 2 = 4 b. = 5 c. 2a
3 +1=7
5 3
5b – 3 = 2 2p + 3 3m – 2
d. 2 e. = 5 f. =4
4 7
77
For free distribution.
g. 3x + x = 7 h. 2m – 3m = 1 i. 4 3x – 1 = 12
2 4 3 5 2
1 2a m–3 x+1 x
j. = 2 k. + 1 = 4 l. + 3 = 8
3 3 –3 2 2
y+1 y–3 1 x+3 x+1
m. + = n. – =2
2 4 2 2 3
15.3 Solving simultaneous equations
You have learnt in previous grades and in the earlier section of this lesson how to
find the value of the unknown by solving a linear equation.
In this section we will learn how to solve linear equations with two unknowns.
x y x+y
–1 7 6
0 6 6
1 5 6
2 4 6
3 3 6
4 2 6
5 1 6
6 0 6
Table 1
By observing the above table, we can conclude that there are infinitely many pairs
of values of x and y which satisfy the equation x + y = 6.
If there is another relationship between x and y, we can construct another equation
and by solving both equations simultaneously we can find the values of x and y that
satisfy both equations.
78
For free distribution.
Suppose it is given that the difference of the two numbers is 2. If we take the larger
number as x, we can construct the equation x – y = 2 , based on the given statement.
There are infinitely many pairs of values of x and y which satisfy this equation too
as can be concluded from observing the following table.
x y x–y
6 4 2
5 3 2
4 2 2
3 1 2
2 0 2
1 –1 2
Table 2
By observing Tables 1 and 2, you can see that there is only one pair of values of x
and y which satisfies both x + y = 6 and x – y = 2. This pair is x = 4 and y = 2.
Therefore, the solution of the above two equations is x = 4 and y = 2.
A pair of equations of this type with two unknowns is known as a pair of simultaneous
equations. “Simultaneous” means “occurring at the same time”.
Let us learn how to solve pairs of simultaneous equations using several other
methods which are shorter, by considering the following examples.
Example 1
Solve the pair of simultaneous equations x + y = 6 and x – y = 2.
To facilitate finding the solution, let us label the two equations as 1 and 2 '
x+y=6 1
x–y=2 2
Method I
We can name this method “the method of substitution”.
By making x the subject of equation 2 , we can write it as
x = 2 + y'
By substituting this expression for x in equation 1 we obtain,
2 + y + y = 6.
2 + 2y = 6
This is a linear equation in one unknown.
79
For free distribution.
Let us find the value of y by solving it.
2 – 2 + 2y = 6 – 2
2y = 4
2y 4
2 =2
y=2
Method II
This method can be named “the method of elimination”.
x+y=6 1
x–y=2 2
First, observe that + y occurs in equation (1) and − y occurs in equation 2 .
By adding both equations we get
x+y+x–y=6+2
Here we have used the axiom “Quantities which are obtained by adding equal
quantities to equal quantities, are equal”.
Now we obtain a linear equation in x, since + y and –y cancel off.
Let us solve it and find the value of x.
2x = 8
2x 8
2 = 2
x=4
To find the value of y, let us substitute x = 4 in equation 1 ,
4+ y = 6
4–4+y=6–4 x=4
y=2 y=2
Note that in the above pair of simultaneous equations, the coefficient of y was 1 in
one equation and −1 in the other. That is, the numerical values of these coefficients
are equal (when the signs are ignored).
80
For free distribution.
Let us consider a few more examples. We will use the 2nd method to solve them.
Example 2
Solve 2m + n = 10
m–n=2 '
2m + n = 10 1
m–n=2 2
Adding 1 and 2 , 2m + n + m – n = 10 + 2
3m = 12
3m 12
3 = 3
m=4
By substituting m = 4 in 1 ,
2 4 + n = 10
8 + n = 10
n = 10 – 8 m=4
n = 2 n=2
Example 3
Solve 2a + b = 7
a + b = 4'
2a + b = 7 1
a+b=4 2
In these equations, the coefficient of b is equal. Therefore, to eliminate b, we must
subtract one equation from the other.
81
For free distribution.
Example 4
Solve x + 2y = 11
x – 4y = 5 '
x + 2y = 11 1
x – 4y = 5 2
Here the coefficients of x are equal. Therefore, let us subtract one equation from the
other to eliminate x.
1 – 2 , x + 2y – (x – 4y) = 11 – 5
x + 2y – x + 4y = 6
6y = 6
6y 6
6 = 6
y=1
By substituting y = 1 in 1 ,
x + 2 1 = 11
x + 2 = 11
x + 2 – 2 = 11 – 2
x=9
Exercise 15.3
1. Solve each of the following pairs of simultaneous equations.
a. a + b = 5 b. x + y = 8 c. m + 2n = 7
a – b = 1 2x + y = 2 m – n = 1
d. 4c – b = 7 e. 2a + 3b = 16 f. 3k + 4l = 4
4c – 2b = 2 4a + 3b = 26 3k – 2l = 16
g. x + 3y = 12 h. 3m – 2n = 10
– x + y = 8 – 3m + n = – 14
2. The sum of two numbers is 10 and their difference is 2. Taking the two numbers
as x and y, construct a pair of simultaneous equations and solve them.
3. Two pens and a pencil cost Rs 32. A pen and a pencil cost Rs 20. Taking the price
of a pen as Rs p and the price of a pencil as Rs q,construct a pair of simultaneous
equations and by solving the pair find the price of a pen and the price of a pencil.
82
For free distribution.